2008
DOI: 10.1504/ijbg.2008.016622
|View full text |Cite
|
Sign up to set email alerts
|

Organisational culture, national culture and performance in International Joint Ventures based in Israel

Abstract: In the light of globalisation, international joint ventures (IJV) appear to offer an opportunity to capitalise on the particularities of localised skills, knowledge and capabilities within the international arena. Moreover, the internationalisation of markets offers an increased scope to innovate, develop and market new products which may benefit from the advantages offered by international collaborations. Nonetheless, some of these IJV fail and many do not achieve satisfactory performance. One reason proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…They talk about scale; nation, region and firm as unit of analysis, asking how far should we reach? Furthermore, organizational culture is influenced by national culture (Gamage, 2006;Avny and Anderson, 2008). Hofstede et al (1990) demonstrated a relationship between national culture values and organizational practices, whilst Lau and Ngo (1996) argue that firms' organizational culture reflects the parent company's home culture.…”
Section: Culture and Innovationmentioning
confidence: 99%
“…They talk about scale; nation, region and firm as unit of analysis, asking how far should we reach? Furthermore, organizational culture is influenced by national culture (Gamage, 2006;Avny and Anderson, 2008). Hofstede et al (1990) demonstrated a relationship between national culture values and organizational practices, whilst Lau and Ngo (1996) argue that firms' organizational culture reflects the parent company's home culture.…”
Section: Culture and Innovationmentioning
confidence: 99%
“…Differences in organizational culture of IJV partners are often perceived as a major cause of conflict in the venture (Avny and Anderson 2008;Heiman et al 2008;Damanpour, Devece, Chen, and Pothukuchi 2010). Since misunderstanding and conflicts tend to arise when there is poor organizational culture fit, transfer or sharing of knowledge is hampered in such a situation (Cummings and Teng 2003;Simonin 1999Simonin , 2004Syed-Ikhsan and Rowland 2004;Cui et al 2006;Wijk, Janseng, and Lyles 2008).…”
Section: Hypothesesmentioning
confidence: 99%
“…A common belief articulated in the literature is that the greater the cultural differences between firms, the more different their management practices will be (Heiman, Li, Chan, and Aceves 2008). Differences in national and organizational cultures between partners are perceived to cause conflicts in IJVs (Park and Ungson 1997;Avny and Anderson 2008;Heiman et al 2008) which may negatively affect their performance. At the same time, studies have also shown that the greater the perceived similarities in cultures between partners, the higher the IJV performance (Cheah-Liaw, Petzall, and Selvarajah 2003;Heiman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mexican workers attitudinally represented the Mexican worker portrayed by Harrison and Hubbard (1998). Over time, they adopted the home company culture, complete with corporate language, shared meaning, and job attitudes that resembled those of production and/or professional workers (Avny et al, 2008). It did, however, take time.…”
Section: Journal Of Management Researchmentioning
confidence: 99%
“…To date, few empirical studies on organizational commitment have been conducted longitudinally in host country environments. Generally, studies seem to be either cross sectional, non-longitudinal measures of commitment (for an exception look to Avny and Anderson, 2008 for work on international joint ventures) or comparisons between cultures using common cultural typologies. Yingyan Wang (2004) compares commitment in cross sectional analysis in state and privately owned organizations in China.…”
Section: Introductionmentioning
confidence: 99%